Significados construídos por crianças sobre suas experiências no projeto "Construindo o Amanhã" - Denzin, Aline de Souza (Universidade Federal de São Carlos, 2014)
Researching with children means a meeting with our inner child, our biggest wishes, and also our biggest fears. The concern in listen to what children have to say about their experiences is awaken by the desire to know their impressions about the world they live in, their experiences in the world and with the world, as children, as some community childhood elements. This Master Degree research was oriented by the following research question: How do children mean their participation in the Project Building Tomorrow ? Presenting as target to analyze the meanings built by children about their participation in the Project Building Tomorrow , developed at the County Elementary School (EMEF) from the Whole Attention Center to Children (CAIC) Laura Suriani Barbuio , a public school located in a suburban area in Santa Rita do Passa Quatro-SP, observing and trying to understand how they mean to be part of the Project. We decided for the qualitative descriptive approach, adopting as data gathering instruments the participants observation registered in field diaries and discussion groups with the contributors in audio recordings. The data gathering was made in the months of April, May and June 2013, in the Project Building Tomorrow . This research contributors are children aged between 7 and 10 years old (Elementary School I), who participate in the Project. It has been realized that Project classes and activities are moments when the girls besides leaning what are supposed to with the activities; they also learn how to coexist with each other and organize themselves as a group. As they recognize and understand themselves as a group, the children are building a feeling of belonging, affection and a bond that make them look for each other in order to find their common things. Also recognizing that there are differences and divergences, they start to look at what is different and what makes them choose between options, by taking decisions that are essential to the continuity of their coexistence. By choosing what is most significant for them, the contributors group draw their own way to be children and live their childhood.
Keywords: Processo educativo; Infância; Práticas sociais; Convivência; Social practices and educational process; Childhood; Coexistence; CIENCIAS HUMANAS::EDUCACAO